Becoming a Woman: Transwomen's Digital Activism Against the Hegemony of Heteronormative Narratives Through Self-Representation - Kulau, Febriansyah; Aini, Syarifah Nur; Akalili, Awanis (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
Behavior carried out by the public who adheres to heteronormative ideas towards gender minorities, such as transwomen, often results in acts of persecution and hegemony in the real world. This action is the result of self-expression carried out by transwomen. With the existence of social media, self-representation can be done by transwomen without thinking about the persecution they will get. But on the other hand, the hegemony obtained by transwomen on social media still occurs. Based on this, the recent study looks at the self-representation carried out by transwomen on social media, especially their personal Instagram, as a form of digital activism. This article focuses on the narratives conveyed by three transwomen, namely, Alegra Wolter, Ian Hugen, and Anggun Pradesha. These three subjects were chosen because they have unique backgrounds and used them to produce narratives about transwomen. Using qualitative content analysis techniques, this research analyzes their self-representation on Instagram as a form of digital activism, specifically as a 'counter-discourse'-a form of resistance that challenges the dominant discourse. This article reveals that both Alegra Wolter, Ian Hugen, and Anggun Pradesha have similarities and differences in Instagram representation. This difference in representation is likely due to the different backgrounds of each research subject. To cite this article (7th APA style): Kulau, K., Aini, S. N., & Akalili, A. (2023). Becoming a woman: Transwomen's digital activism against the hegemony of heteronormative narratives through self-representation. Journal Communication Spectrum: Capturing New Perspectives in Communication, 13(2), 105-126. https://doi.org/10.36782/jcs.v13i2.2491